2019
DOI: 10.1002/etc.4350
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual variation in the cytochrome P4501A response to 2,3,7,8‐tetrachlorodibenzo‐p‐dioxin in herring gull embryo hepatocytes

Abstract: Exposure to dioxin‐like compounds is consistently associated with concentration‐dependent induction of cytochrome P4501A (CYP1A) enzymes in primary cultures of avian hepatocytes. We have previously demonstrated that the median effective concentration (EC50) for induction of this response is predictive of in vivo sensitivity to dioxin‐like compounds in birds. We investigated sources of interindividual variation in the CYP1A response to 2,3,7,8‐tetrachlorodibenzo‐p‐dioxin (TCDD) in wild herring gulls and conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…One possibility is that large interindividual differences in metabolic capacity for PAHs occurred but were not detectable because analytical determinations of BaP were performed on liver tissue pooled from 3 embryos. Previous studies have reported large levels of interindividual variation in induction levels of the enzymes that metabolize PAHs in avian embryos (Head and Kennedy ).…”
Section: Resultsmentioning
confidence: 99%
“…One possibility is that large interindividual differences in metabolic capacity for PAHs occurred but were not detectable because analytical determinations of BaP were performed on liver tissue pooled from 3 embryos. Previous studies have reported large levels of interindividual variation in induction levels of the enzymes that metabolize PAHs in avian embryos (Head and Kennedy ).…”
Section: Resultsmentioning
confidence: 99%
“…posure route/duration/frequency and toxicological susceptibility has been reported for humans based on factors including genetics, developmental stage, dietary pattern, and behavior . Variation in gene expression among individuals is also reported in avian species (Head & Kennedy, 2019). A recent study showed that the hepatic transcriptome was less variable in ELS than in adult Japanese quail (Legrand et al, 2022).…”
Section: Interindividual Variability Interindividual Variability In Ex-mentioning
confidence: 86%
“…Interindividual variation in herring gull populations has been investigated in response to environmental TCDD contamination. 30 All 55 hepatocyte cultures varied in CYP1A4 expression in a concentration-dependent manner. CYP1A4 was confirmed to be the dominant isoform in the hepatocytes, and basal rates varied 20-fold for CYP1A4 and 126-fold for CYP1A5.…”
Section: Primary Cell Culturesmentioning
confidence: 99%